2018
DOI: 10.1088/1361-6560/aab242
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of patient-specific imaging dose for real-time tumour monitoring in lung patients during respiratory-gated radiotherapy

Abstract: The additional dose to the PTV was at most 1.9% of the prescribed dose over the course of treatment for real-time tumour monitoring. For OARs, we could confirm the high dose region, which may not be susceptible to radiation toxicity. However, to reduce the skin dose from SyncTraX, it is necessary to increase the gating efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Onimaru et al. reported that the PTV dose increases by 1.9% due to the radiation exposure caused by tracking during radiation using SyncTraX [ 28 ]. When converted to whole breast irradiation, the radiation exposure was calculated as approximately 90 mGy.…”
Section: Discussionmentioning
confidence: 99%
“…Onimaru et al. reported that the PTV dose increases by 1.9% due to the radiation exposure caused by tracking during radiation using SyncTraX [ 28 ]. When converted to whole breast irradiation, the radiation exposure was calculated as approximately 90 mGy.…”
Section: Discussionmentioning
confidence: 99%
“…In this case the validated MC simulation could be advantageous and used to obtain patient specific 3D dose to estimate the target and OARs dose received from both treatment and continuous intra-fraction imaging. Imaging dose for these applications may need to be included in treatment planning systems for planning optimizations to deliver correct dose to target while sparing normal tissues (Ding et al 2018, Shiinoki et al 2018. The dose values are plotted for all available kVps in figure 10 from 60 kVp to 140 kVp, since the clinical protocols in table 1 do not include all available kVps.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been reported that the imaging dose for IGRT is smaller than that for treatment, its impact to normal tissue is not negligible . The imaging dose of IGRT devices has been reported previouly . In particular, the imaging dose for CBCT acquisition is larger than that for other imaging devices.…”
Section: Introductionmentioning
confidence: 99%